The Value of responsibility character in animal friendship storybook - Ridayani Ridayani; Demsy Jura; Shaumiwaty Shaumiwaty; Syanurdin Syanurdin; Nanda Saputra; Iwan Fajri (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The value of responsibility is very important to be taught to early childhood because it will shape their character and attitude in the future. If young children lack character responsibility, they may not be able to own up to their mistakes, not apologize when they make mistakes, not take care of their own or others' mistakes, and may not enjoy assignments given to them by their parents or teachers. The purpose of this research is to identify the values of responsibility. The method used in this research was descriptive qualitative with data collection techniques, namely, reading techniques, note-taking techniques and classification techniques. From the results of research conducted by researchers, there are seven indicators that contain the value of responsibility, namely: (1) Admitting when making a mistake, (2) Apologizing when making a mistake, (3) Putting back the equipment/toys that have been used, (4) Keeping his own property, (5) Can keep other people's property, (6) Happy to carry out the tasks given by parenats or teachers, (7) Taking care of school toys. Of the 25 subtitles, there are 17 subtitles that contain the value of responsibility with direct and indirect delivery techniques. The implications of this study suggest that it is essential to teach and instill the value of responsibility to early childhood, as it can shape their character and attitude in the future